What a Difference Kyoto Made: Evidence from Instrumental Variables Estimation - Rahel Aichele; Gabriel Felbermayr (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
The Kyoto Protocols success or failure should be evaluated against the unobserved counterfactual of no treatment. This requires instrumental variables. We find that countries membership in the International Criminal Court (ICC) predicts Kyoto ratification in a panel model. Both multilateral policy initiatives triggered concerns about national sovereignty in many countries. We argue that ICC membership can be excluded from second-stage regressions explaining emissions and other outcomes. This is supported by first-stage diagnostics. Our results suggest that Kyoto had measurable beneficial effects on the average Kyoto countrys energy mix, fuel prices, energy use and emissions, but may have speeded up deindustrialization.
Keywords: C26; Q48; Q54; 330; CO2 emissions; energy; evaluation model; instrumental variables; Kyoto Protocol; Klimaschutz; Umweltabkommen; Internationale Gerichtsbarkeit; Mitgliedschaft; Wirkungsanalyse; Umweltverträgliche Energiepolitik; Schätzung; Welt